The impact of pharmacist-led antimicrobial stewardship program on antibiotic use in a county-level tertiary general hospital in China: A retrospective study using difference-in-differences design - Wang, Ying; Zhou, Chongchong; Liu, Chengying; Liu, Shuanghai; Liu, Xiaoliang; Li, Xin (Frontiers in Public Health, 2022)
Background: Inappropriate use of antibiotics has become a major driver for the spread of antimicrobial resistance globally, particularly common in China. Antimicrobial stewardship programs are effective in optimizing antimicrobial use and decreasing the emergence of multidrug-resistant organisms and the pharmacist has performed a leading role in this program. Objective: To evaluate the impact of antimicrobial stewardship programs driven by pharmacists on antibiotic consumption and costs and the appropriateness of antibiotic use. Methods: A single-center prospective quasi-experimental design was conducted in two independent hepatobiliary surgery wards and two independent respiratory wards in a county-level tertiary general hospital in Jiangsu province, China. Each intervention group was served with antimicrobial stewardship programs with prescriptions audit and feedback, antibiotics restriction, education, and training. The propensity score matching method was employed to balance confounding variables between the intervention group and control group and a difference-in-differences analysis was used to evaluate the impact of antimicrobial stewardship programs. The primary outcome was measured by scores of rationality evaluation of antibiotics. Results: The DID results demonstrated that the implementation of the antimicrobial stewardship programs was associated with a reduction in the average length of hospital stay (coefficient=-3.234, p=0.006), average defined daily doses (coefficient=-2.352, p=0.047), and hospitalization costs (coefficient=-7745.818, p=0.005) in hepatobiliary surgery ward while with a decrease of average defined daily doses (coefficient=-3.706, p=0.029), defined daily doses per patient day (coefficient=-0.330, p=0.004) and antibiotic costs (coefficient=-793.271, p=0.026) in the respiratory ward. The program was also associated with a decrease in scores of rationality evaluation (both p<0.001) in two wards. Conclusions: The result reveals that the implementation of the antimicrobial stewardship programs is effective in reducing the length of hospital stay, decreasing antibiotics consumption and costs, and improving the appropriateness of antimicrobial use such as decreasing irrational use of cephalosporins, reducing combinations, and improving timely conversion. However, great attention ought to be paid to the improper use of broad-spectrum antibiotics and the government is responsible for providing sustainable formal education for pharmacists, and more funding and staff support to promote the construction of antimicrobial stewardship programs.